Investigating the aesthetic appraisal of computers based on the Unified Model of Aesthetics (UMA) - Hu, Yanfeng; Yahaya, Mohd Faiz; Na, Dai (Human Resources Management Academic Research Society (HRMARS), 2023)
This study aims to explore the relationship between consumer preferences and shape typicality cognition through the Unified Model of Aesthetic (UMA), with the goal of addressing the gaps in current research on computer products in terms of cognition, perception, social aspects, and aesthetic responses. The preferences of 100 participants for 10 computer images will be measured on a 7-point Likert scale using four sets of two-way adjectives (typical-novel, unified-variety, social belonging-individuality, and like-dislike). The data will undergo several statistical analyses via the IBM SPSS Statistics software. The findings shall demonstrate the role and significance of typicality, novelty, and other independent variables in influencing aesthetic preferences. The objectives of this study are: (1) To investigate whether the principles of unity and variety contribute to the aesthetic appreciation of computers at the perceptual level; (2) To identify the role of typicality and novelty in consumers' aesthetic preferences for computers; and (3) To explore how social connectedness and autonomy affect the aesthetic pleasure of computers. A thorough review of past studies on Project UMA revealed several gaps that must be addressed. Primarily, not many studies have looked on the relationship between typicality and preference at the cognitive level of computers. Secondly, limited research has explored the perceptual and social levels. This includes testing the relationship between the uniform appearance of computers and popularity at the perceptual level and whether computers can foster a sense of group belonging among the participants at the social level. Previous research demonstrated that people prefer typicality or familiarity and often associate familiarity with safety (Hekkert et al., 2003). Additionally, security stands as an important factor in this study where the research objective shall prove the relationship between security and aesthetic preference, which has great significance for computer appearance design and development.